Intermittent tactile nummular allodynia: expanding the spectrum of nummular headache? - Valença, Marcelo Moraes; Santana, Claudia Cristina de Lira; Mota, Laura Luiza Barbosa Menezes da; Ribeiro, Luana Gomes; Vasconcelos Junior, Florisvaldo José Morais; Andrade, Juliana Ramos de (Headache Medicine, 2025)
IntroductionNummular headache (NH) is a rare primary headache characterized by pain in a well-defined, small, round, or oval area of the scalp, often associated with abnormal local sensations such as paresthesia or allodynia. However, sensory scalp disturbances without pain, such as intermittent tactile nummular allodynia (ITNA), remain poorly understood. This report aims to describe a case of ITNA and discuss its clinical significance in the spectrum of nummular syndromes.Case ReportA 53-year-old woman presented with a 9-year history of intermittent tactile allodynia in the right parietal region, affecting a round area of approximately 6 cm in diameter. The episodes occurred 6–7 times per year, each lasting about four days. The patient experienced significant discomfort upon touching or combing the area but denied spontaneous pain or headache. Neurological examination was unremarkable. Brain MRI showed no abnormalities. The patient also had a history of fibromyalgia. No other systemic or dermatological conditions were identified. The clinical picture was consistent with localized, episodic tactile hypersensitivity without persistent symptoms or headache.ConclusionThis case expands the clinical spectrum of focal scalp sensory disturbances and suggests that ITNA may represent a distinct entity or a non-painful variant of nummular headache. The absence of spontaneous pain, the circumscribed location, and the touch-evoked dysesthesia support a localized sensory dysfunction, possibly involving cutaneous nerve branches. Greater awareness of ITNA is essential to prevent misdiagnosis and unnecessary treatment; further studies are needed to define its pathophysiology and diagnostic boundaries better.